Real-time Mitigation of Effects of False Data in Smart Grid: A Data Diode Approach - Mukherjee D.; Kumar Sethi B.; Chakraborty S.; Banerjee R.; Kumar Guchhait P.; Bhunia J. (My University, 2025)
State estimation algorithms play a crucial role in monitoring the modern grid. Operators employ state estimation algorithms to determine the current prevailing conditions of the grid. Recently false data injection attacks have shown their detrimental effects on the state estimation techniques by bypassing the standard statistical bad data detection algorithm. Such kind of an attack vector injection is possible when the attacker can possibly access the meters or the communication channels and has sufficient resources to modify the measurement data. This work showcases the real time attack vector implementation using OPNET followed by its effective diminution using the data diode scheme. Using such test-bed it can be shown that the proposed data diode scheme can not only prevent the injection of attack vectors in the communication channels but also can effectively mitigate the effects of false data intrusion on the grid. Although such schemes are costly, still it shows a potential physical defending policy of the meters from such genres of attack. An extensive analysis on the standard IEEE 14 bus test system provides a clear insight regarding such aforementioned propositions. © 2021 IEEE.